Captain America. The Winter Soldier [videorecording (DVD)] - Evans, Chris, 1981-; Johansson, Scarlett, 1984-; Stan, Sebastian, 1982-
Captain America teams with the Black Widow and a new ally, the Falcon, in a fight for the future of mankind. Following the cataclysmic events in New York with the Avengers, Steve Rogers, aka Captain America, is living quietly in Washington, D.C. and trying to adjust to the modern world. But when a S.H.I.E.L.D. colleague comes under attack, Steve becomes embroiled in a web of intrigue that threatens to put the entire world at risk. As the conspiracy deepens and it's no longer clear whom to trust, Captain America, Black Widow and the Falcon must join forces to overthrow their insidious enemy's most mysterious and powerful weapon yet - the Winter Soldier.